Relationship between serum albumin as an antioxidant and periodontitis (Mustansiria Dental Journal, 2018)
Objective: The aim of this study was to assess the plasma antioxidant status inpatients with periodontitis using serum albumin concentration as a criterionindex. .Materials and methods: This study was conducted on 20 individuals (10 healthycontrol and 10 with chronic periodontitis). Serum albumin level was detected bythe bromcresol green albumin (BCG) colorimetric method.Results: Patients with periodontitis had a significant decrease in the level of serumalbumin than that of the healthy subjects (p